Curriculum revision for customer relations course - Monge, Jessica (My University, 2012)
The purpose of this capstone project is to re-design a course that is currently taught at Madison College for students from the machinist program. The Customer Relations course is required for program completion and it is one of the only formal classes the students of this technical diploma program are required to take in order to graduate with their technical diploma. The rest of this group of cohorts curriculum is practical, hands-on work in the mechanic shop. Because of the importance of the course for these students, this integrative project will include specific lessons including instructional plans, materials, and assessments. The two credit course will be designed for eight weeks instead of the current format of sixteen weeks to keep students focused and engaged in the course. The curriculum of the Customer Relations course will help students become better-rounded in their profession by giving them a background in customer service, sales, retention, and marketing. In these economic times, employers are looking for more than just a mechanic; they are looking for a diversified employee. Therefore, the course will cover resume writing, business plan development along with market research, and a general background of customer service. The course will incorporate technology, group collaboration and projects that require basic research. This course is required for these program students to help them obtain employment after graduation. Traditional classroom environments are a challenging atmosphere for these students because they are hands-on learners. These groups of students are also non-traditional ranging in age from eighteen to fifty years old. Because of these challenges, the curriculum needs to be engaging, meaningful, applicable to their profession, and non-traditional (meaning not lecture based). My goal in re-designing this course is to provide non-traditional students the knowledge and skills they will need to enter the workforce after their year long program. By giving them skills such as resume writing and business plan development, these students will be more competitive in their industry.
This file was last viewed in Adobe Reader X
Keywords: Curriculum planning; Customer relations; Community college students--Education; Education--Curricula